2007
DOI: 10.1016/j.yjmcc.2007.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Stretch-induced MAP kinase activation in cardiac myocytes: Differential regulation through β1-integrin and focal adhesion kinase

Abstract: Mitogen-activated protein (MAP) kinases have been implicated in hemodynamic load induced heart failure. Both angiotensin II (Ang II) and mechanical stretch activate MAP kinases in cardiac myocytes. In this study, we used a neonatal rat ventricular myocyte (NRVM) model to determine the role of focal-adhesion kinase (FAK) in β 1 integrin mediated MAP kinase activation in response to mechanical stretch in presence and absence of Ang II receptor blockade (ATB). NRVM plated on deformable membranes coated with colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 51 publications
(71 reference statements)
2
80
0
Order By: Relevance
“…This is consistent with the widely recognized role of FAK and other members of the integrin-associated focal adhesion complex as mechanotransducers (Flück et al, 1999;Lal et al, 2007). Phosphorylation of p38 increased in response to HFC-induced mechanical stress (Nader and Esser, 2001;Wretman et al, 2001) or passive mechanical stretch (Aikawa et al, 2002).…”
Section: Mechanical Activation Of a P38-mtor Axissupporting
confidence: 87%
See 1 more Smart Citation
“…This is consistent with the widely recognized role of FAK and other members of the integrin-associated focal adhesion complex as mechanotransducers (Flück et al, 1999;Lal et al, 2007). Phosphorylation of p38 increased in response to HFC-induced mechanical stress (Nader and Esser, 2001;Wretman et al, 2001) or passive mechanical stretch (Aikawa et al, 2002).…”
Section: Mechanical Activation Of a P38-mtor Axissupporting
confidence: 87%
“…Phosphorylation of p38 increased in response to HFC-induced mechanical stress (Nader and Esser, 2001;Wretman et al, 2001) or passive mechanical stretch (Aikawa et al, 2002). The correlations between FTI, FAK and p38 may represent a single pathway, as a hypertrophic signaling pathway involving integrin-FAK and p38 induced by mechanical stress has been reported (Aikawa et al, 2002;Lal et al, 2007). Activation of p38 may contribute to increased protein synthesis via phosphorylation of TSC2-and MNK-induced phosphorylation of eIF4E and p70S6k on T421/S424 (Cully et al, 2010;Hernández et al, 2011;Wang et al, 1998) and is required for myogenic differentiation via activation of MEF2 and MRF4 (Lluís et al, 2006), both processes required for muscle hypertrophy.…”
Section: Mechanical Activation Of a P38-mtor Axismentioning
confidence: 95%
“…However, the molecular mechanisms by which ␤1-integrin attenuates UUO-induced fibrosis are not well characterized. Although it had been shown that mechanical stretch induced ␤1-integrin protein expression in different tissues and that ␤1-integrin is highly expressed in renal tubular epithelial cells (22,33,66,67,70), the functions of ␤1-integrin in renal epithelial cells during mechanical stretch-induced fibrogenesis has never been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Although it had been shown that mechanical stretch induced ␤1-integrin protein expression in different tissues and that ␤1-integrin is highly expressed in renal tubular epithelial cells (22,33,66,67,70), the functions of ␤1-integrin in renal epithelial cells during mechanical stretch-induced fibrogenesis has never been reported. To address whether the fibrogenic effect of mechanical stretch is ␤1-integrin dependent, we first examined whether ␤1-integrin was upregulated by cyclic mechanical stretch in HK-2 cells.…”
Section: Stretch-induced Fibronectin and Tgf-␤1 Expression Is ␤1-intementioning
confidence: 99%
“…Phosphorylation, being if cis or trans, is re-quired to open FAK. Also, studies have showed that the auto-phosphorylation of Tyr397 is regulated by external force [33,123,124]. Thus, the opening motion of FAK is considered as the first reaction in our kinetic model.…”
Section: Electrostatic Interactionmentioning
confidence: 99%